Geographically Weighted Negative Binomial Regression for Modeling Maternal Deaths in East Java Province - Calista Deva Salfatah; Purhadi (Department of Statistics ITS, 2026)
The number of maternal deaths in Indonesia increased from 3,572 in 2022 to 4,460 in 2023. East Java, as one of the provinces with the largest population in Indonesia, still faces challenges in reducing the number of maternal deaths, with 499 cases recorded, placing it in second place with a contribution of 11.19% of the total national cases. This study aims to model the number of maternal deaths in East Java using the Geographically Weighted Negative Binomial Regression (GWNBR) method, which considers spatial aspects and overdispersion of data. The GWNBR model, both with and without exposure, was applied using the Adaptive Bisquare, Gaussian, and Tricube Kernel weighting functions. The exposure variable represented by the number of pregnant women to adjust for inter-regional risk. Based on the model goodness-of-fit (AICc), the GWNBR model with exposure using the Adaptive Gaussian Kernel weighting function was the best model. This model identified four groups of districts/cities based on the similarity of significant predictor variables. Significant variables across all regions are the ratio of community health centers and hospitals per 100,000 population, while the percentage of obstetric complication treatment and postpartum family planning participants are only significant in some regions.